Small airway dysfunction and bronchial asthma control : the state of the art - Cottini, Marcello (Asthma Res Pract, 2015)
According to national and international guidelines, achieving and maintaining asthma control is a major goal of disease management. In closely controlled clinical trials, good asthma control can be achieved , with the medical treatments currently available, in the majority of patients , but large population-based studies suggest that a significant proportion of patients in real-life setting experience suboptimal levels of asthma control and report lifestyle limitations with a considerable burden on quality of life. Poor treatment adherence and persistence, failure to use inhalers correctly, heterogeneity of asthma phenotypes and associated co-morbidities are the main contributing factors to poor disease control. Now, it is widely accepted that peripheral airway dysfunction , already present in patients with mild asthma, is a key contributor of worse control. The aim of this paper is to investigate the association between small-airways dysfunction and asthma symptoms/control. We therefore performed a PubMed search using keywords : small airways; asthma (limits applied: Humans, English language) and selected papers with a study population of asthmatic patients, reporting measurement of small-airways parameters and clinical symptoms/control.